Intense rainfall equation for Abaetetuba-PA, Brazil: comparative study (Research, Society and Development, 2021)
Heavy rainfall extreme events are becoming increasingly significant and frequent in the climate change scenario. This work determined a new IDF equation for the Abaetetuba municipality (PA) from the historical rainfall series (1980 to 2019) obtained in the database of the National Water Agency. The data evaluated by the Filliben, Variance and Kolmogorov-Smirnov tests showed a Normal distribution with better fit considering the return periods 2, 5, 10, 50, 100, 200 and 1000 years. For the disaggregation of precipitation in lengths shorter than 1 day we used disaggregation coefficients recommended by the literature. Using two methods of non-linear regression in a comparative way were obtained coefficients of the equation: K (1197.6964), a (0.0933), b (10.9667) and c (0.7599). Comparing the present equation with the one described in previous work points to intensities overestimated by the old equation. Thus, the equation of intense rainfall updated for Abaetetuba will contribute to the more economical dimensioning of hydraulic-hydrological studies where it is necessary to determine the precipitation intensity.